Complications in implant dentistry - Anchieta, Rodolfo Bruniera [UNESP]; Archangelo, Carlos Marcelo; Rocha, Eduardo Passos [UNESP]; Junior, Manoel Martin; Gil, Naiara Reis [UNESP]; de Almeida, Erika Oliveira [UNESP]; Junior, Amilcar Chagas Freitas [UNESP] (My University, 2015)
Objectives: Dental implants have provided an alternative method of prosthetic rehabilitation with high long-term success rates. However, too often the diagnosis, planning, and indications for dental implants are not correct, resulting in numerous instances of failures caused by the lack of planning, as well as the lack of integration among all involved professionals. Thus, the purpose of this study is to show, through a literature review, the most frequent complications with implant-supported prostheses, such as surgical-prosthetic planning, biomechanics associated with implant-supported dentures, misfittings of dental prostheses, fractures or loosening of implant-supported denture screws, implant fractures, connection abutments, and complications associated with soft tissues. This study also provides some relevant solutions to solve each of these complications. Materials and methods: This review is based on MEDLINE databases from 1990 to 2011. The research is limited to studies written in English containing all or some of the keywords. Fifty-eight articles about the topic and two classic articles from 1983 and 1985 are used. Conclusion: The rehabilitative treatment with implants is not simple and requires an interdisciplinary team for a successful and complete implant treatment. Therefore, reverse planning is necessary to foresee the end result of the prostheses before the surgical stage of osseointegrated implant placement. Careful attention to all the rehabilitative treatment stages, from planning to the surgical and prosthetic procedures to the post-operative stages of maintenance, increases the quality of the short-, medium- and long-term treatments.
Keywords: Dental implants; Dental prostheses; Implant-supported prostheses